1984
DOI: 10.1021/ja00315a048
|View full text |Cite
|
Sign up to set email alerts
|

Fluid solution and solid-state electron nuclear double resonance studies of flavin model compounds and flavoenzymes

Abstract: Partially deuterated and various substituted flavin and thiaflavin model compounds have been synthesized. For the first time, high-resolution H, D, and 14N ENDOR and TRIPLE resonance experiments in fluid solutions have been performed on the paramagnetic derivatives of these compounds. Additionally, valuable information has been obtained about hyperfine anisotropies and molecular structures from ENDOR in rigid matrices. Solid matrix ENDOR studies of native flavoenzymes, namely, "Old Yellow Enzyme" (NADPH dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
108
1

Year Published

1984
1984
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 0 publications
14
108
1
Order By: Relevance
“…The proton hfcs also allow some information on the electronic structure of the cofactor to be drawn. First, the A iso hfc from the methyl H(8␣) protons determined by ENDOR, which is usually considered a guide to the overall spin-density distribution (due to its ease of determination) is one of the smallest yet determined (32,58). This further supports the rather isolated situation of the FMN cofactor in the LOV2 domain and points to a rather nonpolar cofactor-binding site (59).…”
Section: Discussionmentioning
confidence: 59%
“…The proton hfcs also allow some information on the electronic structure of the cofactor to be drawn. First, the A iso hfc from the methyl H(8␣) protons determined by ENDOR, which is usually considered a guide to the overall spin-density distribution (due to its ease of determination) is one of the smallest yet determined (32,58). This further supports the rather isolated situation of the FMN cofactor in the LOV2 domain and points to a rather nonpolar cofactor-binding site (59).…”
Section: Discussionmentioning
confidence: 59%
“…The same effect has been reported for the methanol oxidase semiquinone, a member of the GMC oxidoreductase family which is believed to share a common mechanism with cholesterol oxidase. ENDOR experiments unambiguously demonstrate that, after addition of hydroxylamine (a 'pseudosubstrate') to methanol oxidase, a different FAD radical is generated in the enzyme [14]. Fig.…”
Section: Electron Nuclear Double Resonancementioning
confidence: 79%
“…A second group of signals due to more strongly-coupled protons is observed in the regions 8-10 and 19-21 MHz, corresponding to hyperfine couplings of [9][10][11][12] MHz. Previous work, using isotope-labelling of model flavin semiquinones and flavoenzyme semiquinones, has demonstrated that couplings of this magnitude are dirplayed by 8-CH, protons in both anionic and neutral radicals [14,26,271. Strong couplings also occur to the ring proton on C,.…”
Section: Optical Spectroscopymentioning
confidence: 97%
“…Such a contact interaction could result from a nitrogen of the flavin ring. The observed hyperfine couplings (^iso of 0.8-2 MHz) are less than those expected for nitrogens at position 5 or 10 of the flavin ring, typically 20 and 9 MHz respectively for an anionic flavin semiquinone [20][21][22]. Couplings of this magnitude are too large for detection by conventional ESEEM [23].…”
Section: Discussionmentioning
confidence: 99%